Genomic and Functional Analyses of the 2-Aminophenol Catabolic Pathway and Partial Conversion of Its Substrate into Picolinic Acid in Burkholderia xenovorans LB400 - Chirino, Bernardita; Strahsburger, Erwin; Agulló, Loreine; González, Myriam; Seeger, Michael (PLOS ONE, 2013)
2-aminophenol (2-AP) is a toxic nitrogen-containing aromatic pollutant. Burkholderia xenovorans LB400 possess an amn gene cluster that encodes the 2-AP catabolic pathway. In this report, the functionality of the 2-aminophenol pathway of B. xenovorans strain LB400 was analyzed. The amnRJBACDFEHG cluster located at chromosome 1 encodes the enzymes for the degradation of 2-aminophenol. The absence of habA and habB genes in LB400 genome correlates with its no growth on nitrobenzene. RT-PCR analyses in strain LB400 showed the co-expression of amnJB, amnBAC, amnACD, amnDFE and amnEHG genes, suggesting that the amn cluster is an operon. RT-qPCR showed that the amnB gene expression was highly induced by 2-AP, whereas a basal constitutive expression was observed in glucose, indicating that these amn genes are regulated. We propose that the predicted MarR-type transcriptional regulator encoded by the amnR gene acts as repressor of the amn gene cluster using a MarR-type regulatory binding sequence. This report showed that LB400 resting cells degrade completely 2-AP. The amn gene cluster from strain LB400 is highly identical to the amn gene cluster from P. knackmussi strain B13, which could not grow on 2-AP. However, we demonstrate that B. xenovorans LB400 is able to grow using 2-AP as sole nitrogen source and glucose as sole carbon source. An amnBA− mutant of strain LB400 was unable to grow with 2-AP as nitrogen source and glucose as carbon source and to degrade 2-AP. This study showed that during LB400 growth on 2-AP this substrate was partially converted into picolinic acid (PA), a well-known antibiotic. The addition of PA at lag or mid-exponential phase inhibited LB400 growth. The MIC of PA for strain LB400 is 2 mM. Overall, these results demonstrate that B. xenovorans strain LB400 posses a functional 2-AP catabolic central pathway, which could lead to the production of picolinic acid.